Multi-dimensional trust aware routing for clustered IOT framework - Mohan, Ashwala; Bhanu Bhaskara, Dr. (International Journal of Engineering and Technology, 2018)
With the increased interest in the utilization of smart applications, the IoT has gained a lot of popularity in the real world scenario. Due to the integration of different heterogeneous devices in a single network, various types of security issues will arise in the IoT. To ensure more security in IoT, this paper proposes a new trust aware routing framework based on the inherent communication and data properties of devices connected in the network. A new trust metric is derived in this paper by combining two different trusts based on the communication between nodes and the information passing through them. Further to achieve a prolonged network lifetime with optimal resource conservation, a clustering based communication strategy is accomplished. Extensive simulations are carried out by varying the malicious nature of network and the performance is measured through the metrics, packet loss ratio, packet delivery ratio, delay, network lifetime and average energy consumption.Â